Focused ultrasound subthalamotomy in patients with asymmetric Parkinson's disease: a pilot study. Issue 1 (January 2018) - Martínez-Fernández, Raul; Rodríguez-Rojas, Rafael; del Álamo, Marta; Hernández-Fernández, Frida; Pineda-Pardo, Jose A; Dileone, Michele; Alonso-Frech, Fernando; Foffani, Guglielmo; Obeso, Ignacio; Gasca-Salas, Carmen; de Luis-Pastor, Esther; Vela, Lydia; et al.
Summary: Background: Ablative neurosurgery has been used to treat Parkinson's disease for many decades. MRI-guided focused ultrasound allows focal lesions to be made in deep brain structures without skull incision. We investigated the safety and preliminary efficacy of unilateral subthalamotomy by focused ultrasound in Parkinson's disease. Methods: This prospective, open-label pilot study was done at CINAC (Centro Integral de Neurociencias), University Hospital HM Puerta del Sur in Madrid, Spain. Eligible participants had Parkinson's disease with markedly asymmetric parkinsonism. Patients with severe dyskinesia, history of stereotactic surgery or brain haemorrhage, a diagnosis of an unstable cardiac or psychiatric disease, or a skull density ratio of 0·3 or less were excluded. Enrolled patients underwent focused ultrasound unilateral subthalamotomy. The subthalamic nucleus was targeted by means of brain images acquired with a 3-Tesla MRI apparatus. Several sonications above the definitive ablation temperature of 55°C were delivered and adjusted according to clinical response. The primary outcomes were safety and a change in the motor status of the treated hemibody as assessed with part III of the Movement Disorders Society–Unified Parkinson's Disease Rating Scale (MDS–UPDRS III) in both off-medication and on-medication states at 6 months. Adverse events were monitored up to 48 h after treatment and at scheduled clinic visits at 1, 3, and 6 months after treatment. The study is registered with ClinicalTrials.gov, number NCT02912871 . Findings: Between April 26 and June 14, 2016, ten patients with markedly asymmetric parkinsonism that was poorly controlled pharmacologically were enrolled for focused ultrasound unilateral subthalamotomy. By 6 months follow-up, 38 incidents of adverse events had been recorded, none of which were serious or severe. Seven adverse events were present at 6 months. Three of these adverse events were directly related to subthalamotomy: off-medication dyskinesia in the treated arm (one patient, almost resolved by 6 months); on-medication dyskinesia in the treated arm (one patient, resolved after levodopa dose reduction); and subjective speech disturbance (one patient). Four of the adverse events present at 6 months were related to medical management (anxiety and fatigue [one patient each] and weight gain [two patients]). The most frequent adverse events were transient gait ataxia (related to subthalamotomy, six patients), transient pin-site head pain (related to the head frame, six patients), and transient high blood pressure (during the procedure, five patients). Transient facial asymmetry (one patient) and moderate impulsivity (two patients) were also recorded. The mean MDS–UPDRS III score in the treated hemibody improved by 53% from baseline to 6 months in the off-medication state (16·6 [SD 2·9] vs 7·5 [3·9]) and by 47% in the on-medication state (11·9 [3·1] vs 5·8 [3·5]). Interpretation: MRI-guided focused ultrasound unilateral subthalamotomy was well tolerated and seemed to improve motor features of Parkinson's disease in patients with noticeably asymmetric parkinsonism. Large randomised controlled trials are necessary to corroborate these preliminary findings and to assess the potential of such an approach to treat Parkinson's disease. Funding: Fundación de investigación HM Hospitales and Insightec.